2017
DOI: 10.1111/pim.12457
|View full text |Cite
|
Sign up to set email alerts
|

Cover Image Volume 39, Issue 9

Abstract: The cover image, by J. L. Muñoz‐Carrillo et al., is based on the Original Article Resiniferatoxin modulates the Th1 immune response and protects the host during intestinal nematode infection, DOI: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Many studies have shown that Th1 cytokines, such as IL-12, INF-γ, IL-1β, and TNF-α are much more abundant in the early stages of intestinal infection by T. spiralis [63,[67][68][69]. Inflammatory mediators, such as prostaglandin E2 (PGE2) and nitric oxide (NO), as well as the production of Th1 cytokines, such as, IL-12, INF-γ, IL-1β and TNF-α, were found to be produced in greater amounts during the intestinal phase of the T. spiralis infection, which was linked to an increased number of eosinophils and the development of intestinal pathology [64,70]. This suggested that T. spiralis infection induced an increase of small intestine mucosal immune cells and a mixed Th1/Th2 phenotype with a predominance of Th2 response at the early stage of infection.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Many studies have shown that Th1 cytokines, such as IL-12, INF-γ, IL-1β, and TNF-α are much more abundant in the early stages of intestinal infection by T. spiralis [63,[67][68][69]. Inflammatory mediators, such as prostaglandin E2 (PGE2) and nitric oxide (NO), as well as the production of Th1 cytokines, such as, IL-12, INF-γ, IL-1β and TNF-α, were found to be produced in greater amounts during the intestinal phase of the T. spiralis infection, which was linked to an increased number of eosinophils and the development of intestinal pathology [64,70]. This suggested that T. spiralis infection induced an increase of small intestine mucosal immune cells and a mixed Th1/Th2 phenotype with a predominance of Th2 response at the early stage of infection.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…For example, Trichinella spiralis larvae group (TSL-1) antigens induce the DCs maturation [92], leading to the expression of MHC II [93,94], promoting the development of a Th1 type cellular immune response [95]. Several studies, both in vitro and in vivo, have shown that during the early stage of intestinal infection by T. spiralis there is a significant increase of Th1 cytokines such as IL-12 [96,97], INF-γ [95][96][97][98], IL-1β [97][98][99] and TNF-α [96,97,100]. It is possible that this Th1 response is mediated through the TLR-4 activation in DCs by TSL-1, through the signaling pathway TLR4/MyD88/NF-κB [101,102].…”
Section: Parasitic Helminth Infectionsmentioning
confidence: 99%
“…Infective larvae of T. spiralis. Photomicrograph of infective larvae of T. spiralis, from artificial digestion, observed at a 10Â objective under the light optical microscope [10].…”
Section: Epidemiological Aspects Of Trichinellosismentioning
confidence: 99%